Intellectual capital and anticipated future sales in small and medium-sized biotechnology companies - Hermans, Raine; Kauranen, Ilkka; Elinkeinoelämän tutkimuslaitos (Helsinki : Research Institute of the Finnish Economy, 2003)
Tiivistelmä.
Keywords: henkinen pääoma; liikevaihto; pienet ja keskisuuret yritykset; biotekniikka; ekonometria; Biotechnology; Small and medium sized business